Determinants of Maternal Emotion Socialization: Based on Belsky’s Process of Parenting Model - Bao, Jing; Kato, Michiyo (Frontiers in Psychology, 2020)
The purpose of the current study was to investigate how the potential multifactors influence mothers’ emotion socialization. This study involved 300 Japanese-speaking married mothers with 2–5-year-old children, who answered a series of measures of emotion socialization (coaching, dismissing, dysfunction, and non-involvement), emotion regulation strategy (reappraisal and expressive suppression), psychopathology (anxiety and depression), and perceived parenting alliance with their partners. (a) Hierarchical multiple regression analyses demonstrated different effects between maternal anxiety and depression, such that higher levels of depression were associated with less coaching and higher levels of anxiety were associated with more dismissing and dysfunction. (b) Moreover, maternal emotion regulation was significant even when controlling for psychopathology, in which reappraisal had significant positive association with coaching and, conversely, expressive suppression had significant negative association with coaching and positive associations with non-involvement, dismissing, and dysfunction. (c) Additionally, moderation analysis revealed that a greater use of reappraisal was associated with more coaching, and this relation was strongest in lower levels of parenting alliance. Similarly, a greater use of reappraisal was associated with less dysfunction only when parenting alliance was low. Reappraisal may be effective in promoting supportive emotion socialization and buffering the negative effect of lower parenting alliance on unsupportive emotion socialization. Based on Belsky’s process of parenting model, we incorporate maternal psychopathology, emotion regulation, and perceived parenting alliance into one model of influencing maternal emotion socialization and highlight the unique role of emotion regulation.